Investigation of natural raw materials and eteryfikuyuchyh agents on parameters of quality biodiesel - Шевченко, О.Б.; Тертишна, О.В. (Proceedings of National Aviation University (archive), 2009)
The researches results of synthesis processes of biodiesel oil on the basis of different raw materials and basic physical-chemical properties of MEFA are show.